The treatments of COVID-19 patient with diabetes mellitus: a case report - Pratamawerdi, I. Gede Sadu; Hotama, Jason Raymond; Wirawan, I. Made Suma (International Journal of Advances in Medicine, 2021)
Diabetes mellitus or uncontrolled blood sugar is one of the factors causing the severity risk of COVID-19 infection. The researchers from China and Italy also find a profound connection of the old age patients who have chronic illness comorbid are tend to have a higher risk of enduring serve COVID-19, and have a higher number of deaths. Until this report is written, there are no medicines nor vaccines to treat COVID-19 completely. This article reports KTK, a 57 years old woman, Balinese, was diagnosed with COVID-19 and was treated because of the loss of consciousness. Patient had already done the op debridement amputation for left foot digit II-V and the wound of the patient got worsen. Patient also had blood sugar variability which complicated the insulin therapy and inhibits the patient’s recovery. On her way, the patient’s respiratory system got worsen. Diabetes is strongly connected with a higher risk of severe COVID-19 and has a higher death rate compared to controlled blood sugar. The purpose of the guidance for COVID-19 patients with Diabetes is to prove that comprehensive glycemic control and blood glucose monitoring have a good result of the treatments for COVID-19 patients with Diabetes, also reduce the complication from the comorbid of chronic illness (diabetes), and avoiding the undesirable possibilities about the treatments.